AN ANALYSIS OF INDONESIAN PRONUNCIATION DIFFICULTIES FACED BY THAI SPEAKERS IN BENGKULU UNIVERSITY - Eli Diana (UNIVED Press, 2015)
This study aimed to investigate: (1) Indonesian vowel pronunciation difficulties faced by Thai speakers, (2) Indonesian consonant pronunciation difficulties faced by Thai speakers, and (3) Causes of Indonesian pronunciation difficulties faced by Thai speakers. This study used a descriptive method. The data were taken from recorded Indonesian pronunciation by four Thai exchange students at the University of Bengkulu. The data were analyzed through the transcription of the recorded pronunciation in the form of International Phonetic Alphabet (IPA), the data were reduced to pronunciation difficulties by Thai speakers by drawing a conclusion and verification of data. The results of this study revealed that: (1) Thai speakers found it difficult in pronouncing some Indonesian vowel sounds (such as /a/, /u/, /e/, and /ǝ/) and diphthongs (/au/ and /oi/), (2) Thai speakers found it difficult in pronouncing some consonant sounds (such as /g/, /v/, /ŋ/, /r/, and /ñj/) and clusters (double and triple consonants), (3) The difficulties in pronouncing Indonesian vowel and consonant are likely to occur due to the language transfer (interference), simplification, reduction, over generalization, and addition. These are developmental errors which may reduce as they study Indonesian further by practicing intensively and interacting with the native speakers of Indonesia. Keywords: Pronunciation, foreign speakers, language transfer, interference, simplification, reduction, overgeneralization, addition, developmental errors.